2009
DOI: 10.1016/j.jvs.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound versus color duplex ultrasound imaging in the follow-up of patients after endovascular abdominal aortic aneurysm repair

Abstract: The results showed CEUS imaging is a fast, noninvasive, reliable, and valid alternative to multislice CTA for endoleak detection in endovascular aortic stent graft patients, and is superior to unenhanced US imaging. Contrast-enhanced ultrasound imaging should be performed using a recommended contrast medium dose of 2.4 mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 34 publications
3
99
0
2
Order By: Relevance
“…The emergent role of CEUS and its growing indications compared to CT are also shown by several studies in different fields [24][25][26][27], which prove its applications in the body, for liver, kidney, testis, lymph nodes, thyroid, prostate and small bowel. CEUS with low-mechanical index technique, evaluated in some studies for the EVAR follow-up [8,9,28,29], used second-generation ultrasound contrast agents (e.g., SonoVue Ò ) which employ gas microbubbles of sulfur hexafluoride encapsulated by phospholipid shells. They circulate with a good concentration up to 10 min offering, with harmonic imaging, pure vascular enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergent role of CEUS and its growing indications compared to CT are also shown by several studies in different fields [24][25][26][27], which prove its applications in the body, for liver, kidney, testis, lymph nodes, thyroid, prostate and small bowel. CEUS with low-mechanical index technique, evaluated in some studies for the EVAR follow-up [8,9,28,29], used second-generation ultrasound contrast agents (e.g., SonoVue Ò ) which employ gas microbubbles of sulfur hexafluoride encapsulated by phospholipid shells. They circulate with a good concentration up to 10 min offering, with harmonic imaging, pure vascular enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS was carried out with a bolus of 2.4 mL of secondgeneration contrast agent, followed by 5 mL of saline, as suggested by Iezzi et al [28], who documented how 2.4 mL is more convenient than 1.2 mL, since they produce better images as far as intensity and contrast enhancement are concerned. A second injection should be limited to more difficult cases to better characterize the endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that CDU has not reached the diagnostic accuracy necessary to be a reliable alternative to CT angiography in the follow-up of endovascular AAA repair. Iezzi et al (2009), in the only prospective study to address this issue, shows CEUS imaging significantly improves the diagnostic performance of CDU imaging in endoleak detection in patients with endovascular aortic stent-grafts. Reported no significant difference in sensitivity for endoleak detection between analysis of arterial phase image alone, unenhanced and arterial phase images, and arterial and delayed phase images, after the initial follow-up at 1 month.…”
Section: Ultrasound Surveillance After Endovascular Aneurysm Repairmentioning
confidence: 97%
“…Table 2. CDU compared with CT angiography (Sun, 2006;Iezzi 2009). PPV: positive predictive value; NPV: negative predictive value.…”
Section: Ultrasound Surveillance After Endovascular Aneurysm Repairmentioning
confidence: 99%
“…A number of studies have reported use of contrast-enhanced ultrasound for detection of endoleaks. Generally, it is considered to be more accurate than ultrasound without contrast, and similar to magnetic resonance imaging (MR) and CT (Cantisani et al, 2011;Iezzi et al, 2009;Mirza et al, 2010;Sun 2006). McWilliams et al (2002) investigated 53 patients and found contrast enhanced ultrasound to be more sensitive than unenhanced ultrasound in detection of endoleak when compared to CT, but concluded that ultrasound (with or without contrast) was less reliable than CT. On the contrary, several other authors have concluded that contrast enhanced ultrasound may perform better than CT in detection of endoleak (Carrafiello et al, 2006;Clevert et al, 2008;Henao et al, 2006;Ten Bosch et al, 2010).…”
Section: Ultrasound In Post-operative Surveillancementioning
confidence: 99%